ASTRAGALOSIDE-IV INHIBITS TIBIAL DYSCHONDROPLASIA VIA PI3K/AKT /HIF-1α SIGNALING IN CHICKENS - K. Mehmood; H. Karim; A. A. Razzaq; F. Ali; M. Abdullah; M. K. Iqbal; M. U. Saleem; S. Nawaz; M. Nazar; N. A. Malik; M. Waqas (Journal of Animal and Plant Sciences, 2023)
Tibial dyschondroplasia (TD) is a common leg-pathology of meat type broiler birds which is characterized by defective tibial growth plate (GP) cartilage failing to become bone. This study deals with an attempt to treat TD using Astragaloside IV (Astr IV) from Astragalus membranaceus which have been reported to promote osteogenesis but its protective affects against TD have not been studied yet. For this purpose, we selected 180-day old chickens and distributed them in three groups alike (n= 60); control group, TD group and Astr IV group (orally @50mg/ kg body weight from 8-18 days). The chickens were slaughtered on 7, 10, 14 and 18 days. The chicken performance indicators parameters, tibial bone parameters, and expression of proteins were studied by using immunohistochemistry. The results demonstrated that in TD group production parameters including weight improvement and feed consumption were decreased compared to control group during the study period. Tibial bone parameters were lowered non-significantly (P>0.05) during the experiment except tibial GP, which was increased significantly (P<0.05) in TD chickens compared with control group on day 7, 10 and 14. While, Astr IV group indicated that performance indicators and tibia bone parameters were near to control group compared to TD group. On 14 and 18 days both TD incidence and TD score significantly (P<0.05) amplified in TD group compared to Astr IV group. The results of immunohistochemistry analysis regarding the proteins expression showed P-AKT (P<0.01), HIF-1alpha (P>0.05), and VEGF (P<0.01) expressions were increased in TD group. While the expression of AKT, PI3K and VEGFR1 were decreased non-significantly (P>0.05) in TD group chickens. However, the expression of Akt, PI3K and VEGFR1 proteins was up-regulated, while P-AKT, HIF-1alpha, and VEGF were down-regulated in Astr IV treatment group. Altogether, Astragaloside IV diminishes TD through regulating PI3K/Akt/HIF-1α signaling in chickens.
Keywords: Tibial dyschondroplasia; Chickens; Astragaloside-IV; Growth plate; Chondrocytes